Communicating Christ in animistic contexts - Van Rheenen, Gailyn, 1946- (Grand Rapids, MI Baker, 1991)
Includes bibliographical references and indexes.
Keywords: Christianity and other religions -- Animism; Animism -- relations -- Christianity